L'amor antiromàntic: exemples valencians de paròdies del Tenorio. - HERNÀNDEZ, RAÜL (Scripta, 2014)
This article is a brief commentary on two Valencian examples -both written in Catalanof the many parodies composed on José Zorilla's Don Juan Tenorio during the 19th century in Spain. It specially focuses on the relationship between Josep Bernat i Baldovi's L'agüelo Pollastre and Vicent Peydró's Don Juan Treneta and the Romantic notions of Love and Womanhood included in Zorrilla's masterpiece.